Faculty Careers and Work Lives: A Professional Growth Perspective - O'Meara, KerryAnn; Terosky, Aimee LaPointe; Neumann, Anna (ASHE higher education report, 2008)
The purpose of this volume is to review and synthesize the literature on the American higher education faculty over the last fifteen to twenty years. As career-long students of higher education and the professoriate in particular, the authors have each studied the academic profession for many years, conducting hundreds of interviews with faculty in different types of institutions and in reference to all forms of professorial work: teaching, research, service, and blends of them. Based on the authors' concern regarding faculty growth, this monograph is organized as follows. The first chapter explains how the authors came to the conclusions they draw here--namely, that a strong narrative of constraint (including faculty responses to institutional and environmental constraint) has come to dominate scholarship on faculty and that though they view that narrative as important and "real," it misses the view from the other side of constraint: consideration of the faculty's professional growth even amid scarcity, turbulence, and ambiguity. To achieve this aim, the authors explore the history of public rhetoric on faculty, research on reform in faculty roles and rewards, and other major academic developments pertaining to faculty work and careers. They further define what they mean by a "narrative of constraint," offering specific examples, and they end the chapter with a rationale for why reviewing the literature with an eye toward faculty professional growth makes sense for the future of research and practice. The next chapter, "A Framework for Faculty Growth," discusses an alternative narrative, one that centers on faculty professional growth. Each following chapter (on faculty demographics, appointment types, faculty work, and reward systems) begins with a short vignette centered on each chapter's key theme, presented through the experiences of a particular faculty member. These vignettes are informed by the authors' review of the literature and by the hundreds of in-depth interviews that they have collectively conducted over the years. Given the relative maturity of research on faculty compared with other areas of higher education study, the authors present and analyze, in "Perspectives Guiding Studies of Faculty," the key theoretical frameworks that higher education researchers have used over the years to study faculty. The chapter finds themes among the theories in use, presents their disciplinary origins, points out what each thematic cluster of theories reveals and obscures, and considers future research directions on faculty growth. The final chapter discusses the concept of metanarratives in recent research on faculty, ending with a discussion of various counternarratives that could guide future research and public discourse on faculty. (Contains 1 exhibit, 1 note, and subject and name indexes.)